FRI0198 The Relation Between Inflammation, Carotid Intima-Media Thickness and Low-Density Lipoprotein Cholesterol–High-Density Lipoprotein Cholesterol Ratio in Ankylosing Spondylitis Patients. (9th June 2015) - Kucuk, A.; Uslu, A.U.; Arslan, S.; Turkmen, K.; Toker, A.; Kayrak, M.
Abstract : Background: Ankylosing Spondylitis (AS) is a chronic inflammatory disease that mainly affects the spine and sacroiliac joints, and is often causing deformity and loss of function (1). AS, can also affect non-vertebral tissues and organs such as cardiac, ocular and gastrointestinal tract. Cardiovascular (CVS) mortality is increased in other rheumatic diseases (2). Objectives: To evaluate the relation between carotid intima-media thickness and low-density lipoprotein (LDL) cholesterol - high-density lipoprotein (HDL) cholesterol ratio as indicators of atherosclerosis and ischemic modified albumin (IMA) and total antioxidant status (TOS) as markers of inflammation and oxidative stress in patients with AS. Methods: Sixty AS patients and 54 healthy controls were included in our study. BASDAI and BASFI disease activity scores were recorded. The participants serum lipid panel, IMA and TOS levels were measured. Carotid intima-media thickness (CIMT) of patients and healthy subjects were measured. Results: There were no differences between groups in terms of age, gender and Body mass index (BMI). LDL -HDL ratio was higher in AS patients compared to healthy subjects (2.85±1.00, 2.47±0.90, respectively, p<0.047) AS patients had higher IMA values compared to healthy subjects as well (0.44±0.17, 0.32±0.13, respectively, p<0.0001). AS patients had higher TOS values compared to healthy subjects as well (212.57±149.44, 116.70±122.98, respectively, p<0.005). Also CIMT was significantly higher in AS patients compared to healthy subjects (0.99±0.27, 0.76±0.25, respectively, p<0.0001). There was no correlation between CIMT, IMA and TOS. We also did not find correlation between IMA, TOS values and BASDAI and BASFI. However, there was a positive correlation between LDL-HDL ratio and CIMT (r=0.395, p=0.002) (figure 1 ). Conclusions: LDL-HDL ratio and CIMT as markers of atherosclerosis are found to be higher in patients with AS. These findings might be the main reasons of increased CV morbidity and mortality in this population. References: Daikh DI, Chen PP. Advances in managing ankylosing spondylitis. F1000prime reports. 2014;6:78. Mason JC, Libby P. Cardiovascular disease in patients with chronic inflammation: mechanisms underlying premature cardiovascular events in rheumatologic conditions. European heart journal. 2014 Nov 27. Disclosure of Interest: None declared